ON QUASI-RECTANGULAR BANDS - AMINPOUR, M. (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
In this paper we present a new definition of quasi-semigroups and quasi-rectangular bands, principal result are that every quasi-rectangular band is isomorphic to the direct product of a quasi-left zero semigroup and quasi-right zero semigroup [theorem 3.5]. Mathematical Society Classification: 2010 MSC. 18340. Key words and phrases. Quasi-product, quasi-semigroup, quasi-rectangular band, quasi-left zero semigroup.